Seroprevalence of transfusion transmissible infections among blood donors at the blood bank of a Medical College of Kolkata - Prasanta Ray Karmakar; Prabha Shrivastava; Tapobrata Guha Ray (Wolters Kluwer Medknow Publications, 2014)
Seroprevalence of transfusion transmissible infections (TTIs) among blood donors can be used to monitor the prevalence among apparently healthy adult population. The present study was conducted to determine the profile of blood donors and seroprevalence of TTI among them. Retrospective analysis of the donors of a blood bank attached with a tertiary care hospital of Kolkata in 2011 was carried out. Data were analyzed with SPSS version 17. Majority (85%) of the donors were male, two-third in the age group of 21-40 years. Among the donors 2.79% were positive for any of the screened TTIs. Seroprevalence was highest for hepatitis B (1.41%) followed by human immunodeficiency virus (0.60%) and hepatitis C (0.59%) and least for syphilis (0.23%). Seropositivity increased with age up to 50 years. There was no significant difference in seropositivity between male and female. Highly sensitive donor screening and public awareness program can make transfusion of blood products safe.